Tinjauan kebijakan hutang, profitabilitas, dan likuiditas terhadap nilai perusahaan: Studi empiris pada perusahaan properti dan real estate indonesia - Janah, Nada Nur; Mahadianto, Moh. Yudi; Muna, Arinal (Nur Science Institute, 2023)
Investment is significant for the company's financial sustainability. Debt policy, profitability, and liquidity are components used as a reference for investors when making investments. This research aims to determine the influence of company policy, profitability and liquidity on company value. This research uses a quantitative approach, with a total sample of 75 Property and Real Estate Sub-Sector companies listed on the Indonesia Stock Exchange for 2018-2022. The data analysis method uses a multiple linear regression approach. The research results show that debt policy and profitability influence company value. Meanwhile, liquidity does not affect company value.